Aplicación de las normas internacionales de información financiera (NIIF), en la empresa del Ingeniero Olmedo Toledo Diego Fernando, dedicado a las actividades de ingeniería civil, ubicada en la provincia de Pichincha, cantón Quito, sector la Carolina, durante el período 01 de enero al 31 de diciembre del 2013 - Lucero Pacheco, Mishell Alexandra (2016)
The purpose of this investigation is to demonstrate the application and the impact that is given in the process of the transition of NEC to NIIF in the “ main Olmedo Toledo Diego Fernando construction ” on December 31st 2013, with the purpose to provide to the company real, transparent and uniform information of the financial situation and its performance, discovering the countable treatment of each one of the transactions that merge from the daily activities that the company carries out, through a comparison of previous periods, for this the descriptive methodology is used, emphasizing that the entity is dedicated to the labor of civil engineering, meaning that since the planning to the execution of a construction work, what makes it an Holding company and makes it part of a second group of companies that should adapt this normative according to the Supervision of companies, in the development of the work more relevant characteristics are presented of the company….